THE CORRELATION BETWEEN THE SOCIAL STATUS AND SUCCESSFUL OF EXCLUSIVE BREASTFEEDING AGE 6 MONTHS TO 4 YEARS IN REMPANGA VILLAGE, LOA KULU DISTRICT, KUTAI KARTANEGARA - Yuliani winarti; Indisa Titaniea Ishal; Nurul Mukhlisa; Wiranto Wiranto; Yessi Ayu Wulandari (Universitas Muhammadiyah Kalimantan Timur, 2020)
The provision of breast milk is very important for infants and toddlers during the first 6 months of life. Several factors can affect exclusive breastfeeding, one of which is socioeconomic status. This research was conducted to see the relationship between the status of socio-economic and successful exclusive ASI in the Village District of Loa Kulu. The method of this research is Descriptive correlative quantitative research with a Crossectional method and using Total Sampling Design. The population of this study was 93 respondents and the sample taken was 59 respondents Data analysis using the Chi-square test. The results of the analysis at the significance level of 0.05, which obtained a p-value of 1,692> 0.05. This means that there is no significant relationship between socioeconomic status and the success of exclusive Asi. It can be concluded from this study that there is no relationship between socioeconomic status with the success of exclusive breastfeeding because the success of exclusive breastfeeding cannot be seen just from one factor the especially Socio-Economic Status in Rempanga Village.